Facemasks and Walk Distance in Pulmonary Arterial Hypertension Patients - Scott A. Helgeson, MD (Mayo Clinic Proceedings: Innovations, Quality & Outcomes, 2021)
Little is known about the effect of wearing a facemask on the physiological and perceptual responses to exercise in patients with pulmonary arterial hypertension (PAH). We performed a single-center retrospective study to evaluate whether facemask wearing impacted distanced covered, rating of perceived exertion (RPE), and arterial oxygen saturation (SpO2) during a 6-minute walk test (6MWT) in PAH patients. Forty-five patients being treated for group 1 PAH and who performed a 6MWT before and after implementation of a facemask mandate were included in the analysis. Each included patient performed a 6MWT without (test 1) and with (test 2) a facemask between October 1, 2019, and October 31, 2020. At both time points, all patients also underwent a submaximal cardiopulmonary exercise test, echocardiogram, and blood laboratory tests, with a Registry to Evaluate Early and Long-Term PAH Disease Management Lite 2.0 score calculated. The two 6MWTs were performed 81±51 days apart, and all patients were clinically stable at both testing timepoints. Six-minute walk test distance was not different between test 1 and test 2 (405±108 m vs 400±103 m, P=.81). Similarly, both end-test RPE and lowest SpO2 during the 6MWT were not different in test 1 and test 2 (RPE: 2.5±1.7 vs 2.5±2.1, P=.91; SpO2 nadir: 92.8±3.4% vs 93.3±3.3%, P=.55). Our findings show that wearing a facemask has no discernable impact on the arterial oxygen saturation and perceptual responses to exercise or exercise capacity in patients with moderate-to-severe PAH. This study reinforces the evidence that wearing a facemask is safe in PAH patients, even during exercise.